Incidence and predictors of left ventricular thrombus formation following acute ST-segment elevation myocardial infarction: A serial cardiac MRI study. (September 2019) - Phan, Justin; Nguyen, Tuan; French, John; Moses, Daniel; Schlaphoff, Glen; Lo, Sidney; Juergens, Craig; Dimitri, Hany; Richards, David; Thomas, Liza
Abstract: Aims: Left ventricular (LV) thrombus is a complication of acute ST-segment elevation myocardial infarction (STEMI). We determined the incidence and predictors of LV thrombus formation using serial cardiac magnetic resonance (CMR) and two-dimensional echocardiography studies. Methods and results: Two hundred and ten patients underwent CMR (median 4 days [IQR 3-7]) and transthoracic echocardiography (median 4 days [IQR 3-7]) early after STEMI presentation with serial follow-up CMR (median 55 days [IQR 46-64]) and echocardiography studies (median 54 days [IQR 45-64]) performed subsequently. The incidence of LV thrombus was 12.3% (26/210) by CMR and 6.2% (13/210) by two-dimensional echocardiography. Echocardiography had 50% sensitivity and 100% specificity for LV thrombus detection compared to CMR. LV thrombus was found in 23.6% of patients with anterior STEMI (22/93). Ischaemic stroke occurred in 1.4% of patients (3/210). Patients with LV thrombus had lower baseline LV ejection fraction (LVEF) (34.9% vs 47.4%, p < 0.001). Microvascular obstruction was more common in patients with LV thrombus (77% vs 39%, p < 0.001). Patients with LV thrombus had increased LV dimensions with larger LV end-diastolic (19 ml [IQR 9-44] vs 6 ml [IQR -4-18], p < 0.001) and end-systolic volumes (10 ml [IQR 0–22] vs -4 ml [IQR -12-4], p < 0.001). Conclusion: CMR increases the detection of LV thrombi which standard echocardiography may underestimate. Serial studies post-STEMI may improve detection of LV thrombus, which is more prevalent in patients with anterior infarction, moderate LV dysfunction and adverse LV remodelling. This subgroup of patients may represent a high-risk group for targeted serial screening with CMR.